2010
DOI: 10.1021/pr901128x
|View full text |Cite
|
Sign up to set email alerts
|

The Venomics of Bothrops alternatus is a Pool of Acidic Proteins with Predominant Hemorrhagic and Coagulopathic Activities

Abstract: The venom proteome of Bothrops alternatus, a venomous snake widespread in South America, was analyzed by 2-D electrophoresis followed by mass spectrometric analysis and determination of enzymatic activities. The venomic composition revealed that metallo- and serine proteinases play primary roles in the pathogenesis of the envenomation by this pitviper. The identified 100 venom components with molecular masses from 10 to 100 kDa belong to six protein families: metalloproteinases, serine/thrombin-like proteinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 81 publications
7
29
0
9
Order By: Relevance
“…One interesting fact was the significant contribution of C-type (true) lectins in the B. jararacussu (8.8%) and B. neuwiedi (3.5%) venoms, in parallel with its absence (<1%) in the other venoms (Figure 1). Comparing these data with previous venomics studies [16], [18][20], [23], the major venom protein families as SVMPs, PLA2s and SVSPs were detected in our study in equivalent proportions. However, shotgun nanoESI-LTQ/Orbitrap allowed the detection in all venoms tested of some proteins not yet described as PDIEST, ECTONT, PLB and GLUTCYC.…”
Section: Resultssupporting
confidence: 88%
“…One interesting fact was the significant contribution of C-type (true) lectins in the B. jararacussu (8.8%) and B. neuwiedi (3.5%) venoms, in parallel with its absence (<1%) in the other venoms (Figure 1). Comparing these data with previous venomics studies [16], [18][20], [23], the major venom protein families as SVMPs, PLA2s and SVSPs were detected in our study in equivalent proportions. However, shotgun nanoESI-LTQ/Orbitrap allowed the detection in all venoms tested of some proteins not yet described as PDIEST, ECTONT, PLB and GLUTCYC.…”
Section: Resultssupporting
confidence: 88%
“…The various metalloproteinases identified in B. alternatus venom have molecular masses ranging from 22 to 100 kDa, and are capable of causing hemorrhage, edema, myonecrosis, and coagulation disorders. The venom of B. alternatus also contains many serine proteinases that present coagulant and fibrinogenolytic activities; these enzymes are considered less toxic than metalloproteinases (Ohler et al, 2010). Although venomics studies have revealed that metalloproteinases and serine proteinases are considered the most toxic components , we found that B. alternatus venom showed only moderate proteolytic activity.…”
Section: Discussionmentioning
confidence: 55%
“…However, an acidic PLA 2 identified in B. alternatus venom was found to be the major compound responsible for the lethality of this venom in mice, producing cardiovascular alterations such as dyspnea, tachycardia, arrhythmia, and circulatory shock, as well as tissue damage, including hemorrhage and necrosis (Nisenbom et al, 1986a(Nisenbom et al, , 1986b. Nevertheless, it is known that the protein content of B. alternatus venom comprises mostly metalloproteinases and serine proteinases, accounting for 43.1% and 24.1%, respectively (Ohler et al, 2010). The various metalloproteinases identified in B. alternatus venom have molecular masses ranging from 22 to 100 kDa, and are capable of causing hemorrhage, edema, myonecrosis, and coagulation disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature findings, we are able to assume that B. alternatus venom exhibits a variety of phospholipase A 2 and protease enzymes in its composition (30)(31)(32)(33)(34)(35)(36)(37)(38). At initial extraction steps all protein fractions are present in the system and each enzyme isoform is distributed between the phases, according to its structural properties.…”
Section: Resultsmentioning
confidence: 99%